(untitled) (The Pretoria Student Law Review, 2021)
Words fail to describe what an honour it has been to have been part of the ninth edition of the Pretoria Student Law Review. The sense of satisfaction is overwhelming in this being the third edition I have had the privilege to be a part of. Having spent three years as part of this publication I cannot begin to describe and expand upon all that I have learnt in this time, but one thing which I guarantee is the bright and prosperous future of the legal profession of South Africa. With each successive edition I see a thirst and hunger for knowledge from law students, each year those yearnings becoming more intense and providing us with the most thought provoking and well-founded articles. The desire to challenge the status quo, to reject the notions of complacency and outright refusal of facile thought is truly something all these writers should be proud of and us along with them. To read and to write is the essence of not only thought, but of life itself.